The Role and Modulation of Spinal Perineuronal Nets in the Healthy and Injured Spinal Cord - Sánchez-Ventura, Judith; Lane, Michael A.; Udina, Esther (Frontiers in Cellular Neuroscience, 2022)
Rather than being a stable scaffold, perineuronal nets (PNN) are a dynamic and specialized extracellular matrix involved in plasticity modulation. They have been extensively studied in the brain and hence, other functions such as neuroprotection, ionic buffering, and neural maturation have been attributed to cortical PNN. However, their biological function in the spinal cord and the effects of disrupting spinal PNN remain elusive. Hence, the main objective of this review is to summarize the current knowledge of spinal PNN and their possible potential in pathological conditions such as spinal cord injury (SCI). Here, we also consider various interventions to modulate the extracellular matrix after SCI, targeting the glial scar and spinal PNN to promote regeneration and stabilization of the spinal circuits, respectively. Besides, we discuss the similarities between immature and denervated neurons after a SCI, which overall could be useful for the future of SCI research.